Do nurses have barriers to quality oral care practice at a generalized hospital care in Asmara, Eritrea? A cross-sectional study - Dagnew, Zewdi Amanuel (BMC Oral Health, 2020)
BACKGROUND: Oral care is a fundamental nursing practice that has a great impact on patient well-being and general health during hospitalization. Nurses are responsible for providing oral care in the hospital, however, they usually implement it unsatisfactorily due to inadequate resources, lack of standard protocol, time shortage and ineffective training. The aim of the study was, therefore, to assess nurses’ barriers to quality oral care practice at a generalized hospital. The information obtained will help in highlighting the magnitude of the problem and in the promotion of oral health, prevention and control of oral diseases, reduction of hospital stays and diseases, and in strengthening healthcare systems. METHODS: A cross-sectional design using mixed (quant-qual) method was applied at a generalized hospital. Data for the quantitative study were collected from all (N = 73) diploma and associate nurses through face to face interview with a structured questionnaire. On the other hand, in the qualitative part, head nurses (n = 6) and staff nurses (n = 7) discretely participated in the focus group discussions (FGDs), whereas matron (n = 1), assistant matrons (n = 2), and supervisor (n = 1) in total 4, participated in the key informant interview (KII). The quantitative and qualitative data were analyzed, respectively, using descriptive statistics and thematic framework analysis. RESULTS: The majority (93.2%) of participants had barriers performing oral care. The barriers mentioned by the participants were; lack of oral care equipment (91.2%), absence of guidelines (73.5%), shortage of staff (67.6%), time constraints (66.2%), inadequate knowledge (54.4%), poor supervision (47.1%), high work load (44.1%), and not being a priority (33.8%). Moreover, through FGD and KII, four main barriers to oral care were identified namely; inadequacy of resources, knowledge gap in oral care practice, nurse related barriers (perception of nurses and initiative of nurses) and gaps in management. CONCLUSIONS: The study concluded that nurses faced barriers at individual, organizational and ministry level that hindered them from performing standard and effective oral care. Therefore, there is a need for further training, motivation, standardized protocol and provision of equipment and supplies to promote oral health of patients.